Navigating the Digital Landscape: Social Media and Employee Privacy in Nepalese Service Sector - Shrestha, Sajeeb Kumar; Basnet, Deepak; Dhungana, Dipendra (Ganeshman Darpan, 2024)
This study employs a descriptive and causal research design to investigate the impact of social media on employee privacy in Nepalese service sector organizations, using primary data gathered through surveys. With a sample size of 200 employees in Kathmandu Valley, the research reveals that monitoring and controlling online activities significantly affect employee privacy, followed by limitations on off-duty online activities. Sharing personal information also emerges as a contributing factor. The study underscores the importance of balanced organizational policies that uphold employee privacy rights while harnessing the advantages of social media. These findings highlight the need for organizations to adopt clear guidelines to protect employee privacy in the digital age.